The Effect of English Stories With Level Application: a Media for Learning Vocabulary at Seventh Grade of SMP Negeri 4 Pematangsiantar - Hutasoit, Renova Sulinda; Marpaung, Tiarma Intan; Hutahaean, David Togi; Herman, Herman; Siahaan, Basar Lolo (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
The aim of this research is to determine the effect of using English Stories With Level application on students' vocabulary mastery in the seventh grade of SMP Negeri 4 Pematangsiantar in 2024/2025 academic year. The research aimed to determine the effect of using the English Stories With Level Application as a media for learning vocabulary at seventh grade of SMP Negeri 4 Pematangsiantar. The objective of the study was to find out whether this application could significantly improve students' vocabulary mastery. The research utilized a quantitative approach with a quasi-experimental design, which included both a pre-test and post-test. The population consisted of 300 students, from which two classes were selected via cluster random sampling. The experimental group received instruction using English Stories with Level Application, while the control group used conventional media (handbook). Data collection involved administering pre-tests and post-tests to both the experimental and control groups. The descriptive analysis revealed that the mean post-test score for the experimental group was 73.00, while the control group scored 66.50. A paired-sample t-test confirmed a statistically significant difference between the pre-test and post-test scores of the experimental group, with a p-value of 0.000 (p < 0.05), leading to the acceptance of the alternative hypothesis (Ha). This suggested that the use of this application as a media for vocabulary learning was more effective than traditional methods. In conclusion, the research demonstrated that English Stories with Level Application significantly enhanced vocabulary acquisition among seventh grade students.